Bioethanol Production from Rice Straw through Utilization of Agrobiomass Waste in Central Java Towards Clean Energy: a Review - Nabil, Nisrina Hasna’; Handoko, Pratama Senapati Bagus; Destantri, Fitri Wahyuningtyas; Syahputra, Adhika Bintang; Bahlawan, Zuhriyan Ash Shiddieqy (Journal of Clean Technology, 2024)
Bioethanol is an alternative energy to replace fossil fuels from plants. Central Java is the second largest rice producer in the world in Indonesia, with the potential of rice straw waste which can be optimized into bioethanol. Rice straw contains abundant cellulose reaching 32-47%, hemicellulose reaching 19-27%, and lignin reaching 5-24%. Methods for making bioethanol from rice straw include pretreatment, hydrolysis, fermentation, and distillation. Lignin inhibits acid penetration before hydrolysis and microbial growth during fermentation, so it needs to be eliminated using alkaline pretreatment. Glucose production from alkali-pretreated rice straw can be hydrolyzed using chemical or enzymatic catalysts. Acid hydrolysis method using dilute H2SO4 with consideration of a shorter operating time. In addition, the price of enzymes is very high, and the operating time is very long, which will reduce product effectiveness. The acid hydrolysis method using 2% H2SO4 takes 30 minutes at 150 oC, which can produce a yield of 16%. Production of bioethanol from rice straw using separate hydrolysis and fermentation (SHF) methods. Saccharomyces cerevisiae, with a 24-hour fermentation time, produced a yield of 80.9% and a productivity of 0.172 g/L h. Distillation is used to remove impurities from liquids that have been polluted with rice straw-derived solutes with various boiling points. Vacuum distillation can produce a yield of 40% purity. Utilization of rice straw into bioethanol can reduce environmental pollution so that it supports clean energy.